Pharmacological guidelines for managing temporomandibular disorders - Eduardo Dias de Andrade Eduardo Dias de Andrade; Célia Maria Rizzatti-Barbosa; Marcos Luciano Pimenta Pinheiro (Universidade Estadual de Campinas, 2015)
Temporomandibular disorders (TMD) characterize a heterogeneous group of conditions involving the temporomandibular joint (TMJ) and its contiguous tissues. Although the etiology and pathophysiology underlying the development of TMD have not been completely explained, the symptoms associated with these disorders are similar and are most commonly manifested as pain in the orofacial region. Despite the large body of literature on therapeutic modalities for TMD, this article briefly discusses the most common and current pharmacological clinical guidelines for managing TMD.